Performance measurement and management: a case study in a Guardianship Council (Revista Brasileira de Contabilidade e Gestão, 2022)
The present research aimed to verify the existence of a performance measurement system in the Guardianship Council and how this can help to manage and improve the delivery of services to the community. For that, a case study was carried out with a Guardianship Council in a city in the state of Paraíba and interviews were carried out with the five (05) councilors that form the body, with a total duration of two hours and thirty minutes, on the 6th and May 7, 2021. The result of the study showed that the use of performance indicators, despite existing through diaries and folders, still occurs in a very simple way, where they are only filed and serve more for the purposes of accountability to higher bodies, than for strategic direction and monitoring of the body's performance. Regarding the involvement of the population, there is still a distance and lack of accountability for services. The technological aspects, despite supplying the actions developed, need advances in terms of software, which can facilitate the work of the counselors and the creation of computerized databases, allowing more agility in the processes and follow-ups.
Keywords: management; performance; measurement; Guardianship Council; public accounting